Exploring Students’ Learning Experiences in a Thai EFL Classroom: A Narrative Inquiry - Ajeng Ma'rifah; Dewi Rochsantiningsih; Hefy Sulityawati (University of Muhammadiyah Purwokerto, 2020)
EFL students relatively attain learning experiences from activities they perform in the classroom. This article explored the stories of students’ learning experiences in a Thai EFL classroom and looked through their stories about learning experiences which contribute most to the improvement of their language skills. Four out of thirty grade-10th students in the English as Supplementary class at one of Demonstration Schools in Lopburi Thailand participated in this study. In eliciting the participants' stories, narrative inquiry was carried out as the design of this research. The data were collected through observations, interviews, and document analysis. Afterward, they were analyzed through thematic analysis. The first finding showed that there were 22 learning experiences attained by Thai students during the ES class which belonged to 1) eleven learning experiences for reading, 2) two learning experiences for writing, and 3) nine learning experiences for other skills. The second finding of students’ perceptions revealed that the most helpful learning activities in improving the students’ English skills were 1) reading fiction, 2) watching movies, and 3) reading and translation. These activities provided at least two significant learning experiences for the students, including 1) knowing more vocabularies and 2) working in a group. This study implies that studying learning experiences which promote the students’ language skill improvement is essential for English teachers to select or plan best learning experiences.